2016
DOI: 10.1002/ece3.2504
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of an endemic Mediterranean palm recolonizing old fields

Abstract: Throughout Europe, increased levels of land abandonment lead to (re)colonization of old lands by forests and shrublands. Very little is known about the spatial pattern of plants recolonizing such old fields. We mapped in two 21–22‐ha plots, located in the Doñana National Park (Spain), all adult individuals of the endozoochorous dwarf palm Chamaerops humilis L. and determined their sex and sizes. We used techniques of spatial point pattern analysis (SPPA) to precisely quantify the spatial structure of these C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Ants are erratic and infrequent visitors and also unlikely to pollinate this dioecious plant. There have been suggestions that wind could also play a role in pollination of C. humilis (Herrera, 1989;Jácome-Flores et al, 2016). Although most previous evidence does not support this possibility (Anstett, 1999;, we experimentally test it here (see Results).…”
Section: Study Systemmentioning
confidence: 75%
“…Ants are erratic and infrequent visitors and also unlikely to pollinate this dioecious plant. There have been suggestions that wind could also play a role in pollination of C. humilis (Herrera, 1989;Jácome-Flores et al, 2016). Although most previous evidence does not support this possibility (Anstett, 1999;, we experimentally test it here (see Results).…”
Section: Study Systemmentioning
confidence: 75%
“…Data are available from the Dryad Digital Repository: <http://dx.doi.org/10.5061/dryad.8w9ghx3h2> (Jácome‐Flores et al ).…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the quality component (QLY, hereafter) we compiled available data from previous works on C. humilis seed dispersal in the Doñana National Park made in open areas in dehesa (Fedriani and Delibes 2011, Perea et al 2013, Suárez-Esteban et al 2013, Jácome-Flores et al 2016, Castañeda et al 2017) regarding: 1) fruit handling and fruit processing behaviour; 2) seed germination of handled and defecated/regurgitated seeds; and 3) probability of seedling survival. The cumulative probability is calculated from the product of the three probabilities: i.e.…”
Section: Frugivore Effectivenessmentioning
confidence: 99%
“…Theoretical work has highlighted conspecific spatial clustering as a mechanism reducing competitive exclusion and promoting diversity (Hubbell and Foster 1986, Chave et al 2002). Empirical work has demonstrated that between‐species variability in seed dispersal distances leads to differences in spatial clustering of plants, such that species with shorter seed dispersal distances are more tightly clustered in space than species with longer seed dispersal distances (Seidler and Plotkin 2006, Jácome‐Flores et al 2016). In our simulations, we found no variability between seed dispersal distances across plant species under a scenario that lacked niche partitioning (Fig.…”
Section: Discussionmentioning
confidence: 99%